Separation of Artifacts from Spin‐Torque Ferromagnetic Resonance Measurements of Spin‐Orbit Torque for the Low‐Symmetry Van der Waals Semi‐Metal ZrTe3. Issue 2 (17th December 2021) - Cham, Thow Min; Karimeddiny, Saba; Gupta, Vishakha; Mittelstaedt, Joseph A.; Ralph, Daniel C.
Abstract: Spin‐orbit torques generated by exfoliated layers of the low‐symmetry semi‐metal ZrTe3 are measured using the spin‐torque ferromagnetic resonance (ST‐FMR) technique. When the ZrTe3 has a thickness greater than about 10 nm, artifacts due to spin pumping and/or resonant heating can cause the standard ST‐FMR analysis to overestimate the true magnitude of the torque efficiency by as much as a factor of 30, and to indicate incorrectly that the spin‐orbit torque depends strongly on the ZrTe3 layer thickness. Artifact‐free measurements can still be achieved over a substantial thickness range by the method developed recently to detect ST‐FMR signals in the Hall geometry as well as the longitudinal geometry. ZrTe3 /Permalloy samples generate a conventional in‐plane anti‐damping spin torque efficiency ξ | | DL ξ _||^DL = 0.014 ± 0.004, and an unconventional in‐plane field‐like torque efficiency | ξ | | FL | |ξ _||^FL| = 0.003 ± 0.001. The out‐of‐plane anti‐damping torque is negligible. It is suggested that artifacts similarly interfere with the standard ST‐FMR analysis for other van der Waals samples thicker than about 10 nm. Abstract : Hall‐geometry spin‐torque ferromagnetic resonance (ST‐FMR) allows separation of spin‐orbit‐torque signals from spin‐pumping/resonating heating artifacts that dominate standard ST‐FMR measurements for van der Waals samples thicker than about 10 nm. Artifacts due to spin pumping and resonant heating cause standard ST‐FMR measurements to give large overestimates of spin‐orbit torque and an unphysical apparent thickness dependence when applied to van der Waals materials thicker than about 10 nm. Separation of the spin‐orbit torque signal from artifacts can be achieved using Hall‐detected ST‐FMR.